Mechanical Causes of Osteoarthritis in Adults, its Diagnosis and Treatment : Osteoarthritis in Adults - Fayyaz, Maria; Muneer, Bushra; Iqbal, Aqsa; Bilal, Mohammad Asad; Tabassum, Huma; Shahbaz, Sumbal (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Osteoarthritis (OA) is one of the most devastating chronic conditions that affects adults and aged people around the world. After the age of 65 years, osteoarthritis affects women (70%) more frequently than it does in men (60%). The objective of this study is to find the main causes and treatment strategies for OA. The etiology of OA is multifactorial, with metabolic, inflammatory, and mechanical causes. A number of risk factors including occupation, obesity and injury may initiate various pathological pathways. The main goals of treatment are to minimize impairment, enhance function, and effectively manage pain. In cases of moderate to severe pain, acetaminophen and NSAIDs are more beneficial; nevertheless, they carry a higher risk of major side events involving the upper gastrointestinal tract. The most researched and successful nonpharmacological therapies are patient education, self-management, and exercise. Although nonpharmacological interventions are regularly and widely utilized in the therapy of OA patients, there is little evidence that they are helpful. Requiring a periodic assessment and adjustments of therapy rather than the strict continuation of a single treatment, as the patient's requirements and the course of the disease typically alter over time.